Autistic, Aberrant, and Food-Related Behaviors in Adolescents and Young Adults with Prader-Willi Syndrome: The Effects of Age and Genotype - Atsushi Ishii; Hiroshi Ihara; Hiroyuki Ogata; Masayuki Sayama; Masao Gito; Nobuyuki Murakami; Tadayuki Ayabe; Yuji Oto; Asami Takahashi; Toshiro Nagai (Behavioural Neurology)
The effects of age and genotype were examined, with regard to the severity of aberrant, autistic, and food-related behaviors in Prader-Willi syndrome (PWS), with an emphasis on the contrast between adolescents and young adults. The Aberrant Behavior Checklist Japanese version (ABC-J), the Food Related Problem Questionnaire (FRPQ), and the Pervasive Developmental Disorders Autism Society Japan Rating Scale (PARS) were administered to 65 PWS patients, including 20 adolescents (ages 12 to 17) and 45 young adults (ages 18 to 29). Significant differences (Mann–Whitney U tests) were found in ABC-J (p=0.004) and PARS (p=0.021), with lower scores in adolescents than in young adults. While DEL subgroups showed no significant differences between the two age groups in ABC-J (p=0.063) and PARS (p=0.134), mUPD subgroups showed a statistically significant difference in terms of ABC-J (p=0.007). No significant differences were found between adolescents and young adults, in terms of FRPQ (p=0.163). These results suggest that aberrant and autistic behaviors follow a marked worsening trend from around the age of 18. On the other hand, food-related behaviors give no sign of change at this transitory stage. Young adults with mUPD were found to be significantly more severe than adolescents with mUPD, in terms of aberrant behaviors.